Ventricular Enlargement as a Neuroimaging Endophenotype for Schizophrenia in Familial High-Risk Populations: A Systematic Review - Pande Komang Wahyu Pradana; I Gusti Ngurah Bagus Mahayasa (The Indonesian Journal of General Medicine, 2025)
INTRODUCTION: Ventricular enlargement is one of the most robust and consistently replicated neuroanatomical findings in individuals with schizophrenia.T his review systematically evaluates the evidence for an association between enlarged ventricular volume and the genetic risk for schizophrenia in individuals with a family history of the disorder. METHODS: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library databases was conducted to identify observational studies that used computed tomography or magnetic resonance imaging to compare ventricular volumes among schizophrenia patients, their unaffected first-degree relatives, and healthy controls. The secondary aims of this review are to quantify the magnitude of ventricular volume differences among patients, their unaffected first-degree relatives, and healthy controls; to examine the regional specificity of these changes, particularly in the lateral ventricles, third ventricle, and temporal horns; to synthesize evidence on the clinical and biological correlates of ventricular volume, including its relationship with gray matter deficits, symptom severity, gender, and environmental risk factors; and to critically evaluate the cumulative evidence for ventricular enlargement as a valid endophenotype for schizophrenia. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines. Data on study design, participant characteristics, imaging parameters, and quantitative ventricular measurements were extracted. The methodological quality and risk of bias of included studies were assessed using the Newcastle-Ottawa Scale (NOS). RESULTS: Patients with schizophrenia consistently exhibit significantly larger lateral and third ventricles and a higher ventricle-to-brain ratio compared to both healthy controls and their unaffected first-degree relatives. Unaffected relatives frequently demonstrate intermediate ventricular volumes, which are larger than those of healthy controls but smaller than those of their affected family members. Secondary outcomes indicate that ventricular enlargement is significantly associated with widespread cortical gray matter deficits, is more pronounced in males, and may be exacerbated by environmental factors such as substance use and obstetric complications in genetically vulnerable individuals. CONCLUSION: A significant and robust association exists between enlarged cerebral ventricular volume and the genetic risk for schizophrenia. This solidifies the status of ventricular enlargement as a key neurobiological marker of liability, for developing multimodal models for early risk identification.